Pawned Horses: Risk and Liability in Fourteenth Century German Small-Credit Market - Doron, Aviya (Medieval encounters, 2021)
Many Jewish-Christian credit transactions relied on pawns as collateral, which presumably eliminated the risk in the case of debtors’ default. However, keeping and maintaining certain pawns involved particular risks that further complicated these transactions. This paper focuses on live pawns, specifically horses, where the safekeeping of the animal involved far greater difficulties and risks than with other valuable objects that were pawned with Jews. By tracing how legal norms and practices addressed some of the unique risks attached to receiving horses as pawns, this article will outline the expectations both Jews and Christians had when engaging in credit transaction secured by horses. Relying on responsa literature, urban legislation, and court cases from the late thirteenth to mid-fourteenth centuries, this analysis will discuss some of the complications relating to liability over live pawns, with the goal of demonstrating how a specific type of pawn, and its unique risks and benefits, reflects previous assumptions and expectations regarding risk and trust.